2014
DOI: 10.1590/0100-3984.2012.1636
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioendotelioma hepático multifocal e metastático: relato de caso e revisão da literatura

Abstract: Epithelioid hemangioendothelioma is a rare neoplasm of vascular origin whose involvement of organs such as lung, spleen, bone, breast and liver has already been reported. The clinical signs and the prognosis of this tumor are quite variable. From the present case report, the authors have sought to contribute with literature data, by reviewing clinical and radiological features which may be useful to include such a condition in the differential diagnosis of liver lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 6 publications
0
2
0
3
Order By: Relevance
“…Radiological findings of the most common liver lesions are well known and widely described in the literature. On the other hand, scarce studies are found in the literature consolidating the main information regarding more rare liver tumors and lesions ( 18 - 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Radiological findings of the most common liver lesions are well known and widely described in the literature. On the other hand, scarce studies are found in the literature consolidating the main information regarding more rare liver tumors and lesions ( 18 - 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…O hemangioendotelioma epitelioide (HE) é um tumor vascular raro, composto por células epitelioides e por um estroma fibroso hialinizado (TORRES et al, 2014).…”
Section: Introductionunclassified
“…O hemangioendotelioma epitelioide (HE) é um tumor vascular raro, composto por células epitelioides e por um estroma fibroso hialinizado (TORRES et al, 2014). Sua incidência predomina em partes moles, podendo se manifestar, e sendo mais comum, em outros órgãos como o pulmão, o baço, e o fígado (REIS et al, 2016).…”
Section: Introductionunclassified
“…Tendo isso em vista, o HE é considerado um tumor maligno de agressividade baixa/intermediária, com apresentação clínica e prognóstico variados, a depender da fase em que foi diagnosticado e da localização do mesmo (TORRES et al, 2014). A prevalência mundial estimada dessa patologia é inferior a 1 em 1 milhão, ocorrendo duas vezes mais no público das mulheres do que no dos homens (KIM et al, 2015).…”
Section: Introductionunclassified